Macroprudential regulation and the monetary transmission mechanism - Agénor, Pierre-Richard; Pereira da Silva, Luiz A. (Journal of Financial Stability, 2014)
The paper presents a simple dynamic macroeconomic model of a bank-dominated financial system that captures some of the key credit market imperfections commonly found in middle-income countries. The model is used to analyze the interactions between monetary and macroprudential policies, involving, in the latter case, changes in reserve requirements. In addition to a qualitative analysis, a calibrated version is used to study numerically the transitional dynamics and steady-state effects of an increase in the reserve requirement ratio, under alternative parameter values. The analysis shows that understanding how these tools operate is essential because they may alter, possibly in substantial ways, the monetary transmission mechanism.